Tindakan Mengoperasikan Telepon Seluler dalam Pesawat Berdasarkan Undang-Undang Nomor 1 Tahun 2009 tentang Penerbangan - Santoso, Kris Putra; Santoso, Tommy Julio; Subagijo, Cindy Fransisca; Teguh, Tamara (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aimed to analyze the actions of passengers who operated cellular telephones on board the aircraft and the criminal liability of passengers who operated cellular telephones on aircraft based on Law Number 1 of 2009 concerning Aviation. The approach used in this study was a statutory approach and a case approach with a normative juridical type of research. The data sources in this study used primary and secondary legal materials. The data that were obtained were analyzed using descriptive techniques. The actions of passengers who operated cell phones on planes meet one form of error, namely negligence without awareness. Criminal liability for passengers who operated cellular phones onboard the aircraft was based on the elements of a criminal act in Article 54 letter f of the Aviation Law, and the sanctions provided were regulated in Article 412 paragraph (5) of the Aviation Law, which was threatened with a maximum imprisonment of two years or a maximum fine of 200,000,000 IDR.